Effects of six-week periodized versus non-periodized Kettlebell swing training on strength, power and muscular endurance - Tavares Santos Junior, E. R.; De Salles, B.; Dias, I.; Simao; Simão, R.; Willardson, J. (International Journal of Exercise Science, 2022)
The purpose of this study was to compare a periodized versus a non- periodized protocol of kettlebell (KTB) swings over six weeks on strength, power, and muscular endurance. Twenty-eight high intensity functional training (HIFT) practitioners were assigned to non- periodized (NPG = 11), periodized (PG = 11), or control groups (CG = 6). NPG used the same load (20 kg) throughout the training period while the PG used a step loading progression (with an added four kilograms every two weeks). Measures of strength and muscular endurance in the deadlift exercise, and power in the countermovement jump were assessed before and after six weeks. A two-way ANOVA was used to verify pre- to post-test differences in strength, power, and muscular endurance. An analysis of the effect size was also incorporated. For strength and power, statistical differences from pre- to post-test were found for both the NPG (p < 0.001; 1-RM improvement = 8.7%; jump height improvement = 8.7%) and PG (p < 0.001; 1-RM improvement = 7.8%; jump height improvement = 10.1%), with no difference between groups. For muscular endurance, only the PG showed significant differences from pre- to post-test (p = 0.013; muscular endurance improvement = 23.8%). In conclusion, when the goal is to increase strength and power performances in HIFT practitioners, periodized and non-periodized KTB models appear to be equally effective, and this can simplify the strength coach's practice in programming KTB swing training periods. For muscular endurance, the addition of KTB swing on a periodized basis seems to be a more effective strategy.